IS incident recovery and service value: a service-dominant logic view. Issue 4 (4th July 2022) - Najjar, Mohammad S.; Kettinger, William J.; Kettinger, Lynda D.
ABSTRACT: IS service delivery failures inside companies are value diminishing events. Information systems service providers seek to limit this value destruction but lack guidance on IS incident resolution actions that satisfy users and preserve IS service value. We apply Service-Dominant Logic (SDL) to explore what is relevant to users' recovery service experiences while interacting with IS service providers. We use an integrated research approach including qualitative and quantitative data. We uncover actions that lead to a satisfying incident recovery and categorise them into three recovery components (responsive handling interactions, supportive communicating interactions, and effective resolving actions) that reflect IS provider resource exchanges of information, knowledge, and service skills with users in resolving incidents. We integrate these three recovery components as factors in our research model and test direct and moderating effects on value outcomes. We find that users' recovery satisfaction results from both a "fix it fast and fully" perspective and a sense of effort and fairness conveyed. Results point to managers preserving overall IS service satisfaction and service quality by facilitating proper resource exchanges during an incident recovery.